2015
DOI: 10.1186/s12885-015-1511-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-regulating factors in ascites as predictive biomarkers of drug resistance and progression-free survival in serous epithelial ovarian cancers

Abstract: BackgroundPlatinum-based combination therapy is the standard first-line treatment for women with advanced serous epithelial ovarian carcinoma (EOC). However, about 20 % will not respond and are considered clinically resistant. The availability of biomarkers to predict responses to the initial therapy would provide a practical approach to identify women who would benefit from a more appropriate first-line treatment. Ascites is an attractive inflammatory fluid for biomarker discovery as it is easy and minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 58 publications
2
50
0
4
Order By: Relevance
“…These factors cumulatively contribute to creating a pro‐inflammatory and immunosuppressive tumor microenvironment . Among these factors, IL‐6 and IL‐10 have received the most attention due to their correlation with poor prognosis and response to therapy …”
Section: Ascites As a Tumor Microenvironment In Ovarian Cancermentioning
confidence: 99%
“…These factors cumulatively contribute to creating a pro‐inflammatory and immunosuppressive tumor microenvironment . Among these factors, IL‐6 and IL‐10 have received the most attention due to their correlation with poor prognosis and response to therapy …”
Section: Ascites As a Tumor Microenvironment In Ovarian Cancermentioning
confidence: 99%
“…Patients with EOC and higher IFN-γ expression levels in ascites have shorter disease-free progression and overall survival [54]. Measuring cytokines in ascites may also provide a novel approach to discriminate patients with intrinsic resistance to irst-line therapy [55]. The authors found that the combination of serum CA125 and ascites leptin levels was a strong predictor of clinical resistance to irst-line therapy.…”
Section: Cell-free Ascites: Biomarkers and Eoc Progressionmentioning
confidence: 99%
“…The concentration of these proinflammatoy cytokines in ascites is 40-500 folds greater than in serum. IL-6 may be secreted in ovarian cancer cells, tumor-associated macrophages, and peritoneal mesothelial cells, which have the highest potential for secretion of this interleukin [68,69].…”
Section: Malignant Ascites-immunological Factors Cytokines and Acelmentioning
confidence: 99%